Adaptive Volumetric Anatomy Visualization in VR with Tangible Control - Kleinbeck, Constantin; Smietana, Max; Lewis, Noah; Teufel, Timo; Kreimeier, Julian; Heinzl, Christoph; Steiner, Jürgen; Anthes, Christoph; Roth, Daniel (Proceedings - 2023 IEEE International Symposium on Mixed and Augmented Reality Adjunct, ISMAR-Adjunct 2023, 2023)
High-quality visualization of medical image data is essential for preoperative planning of complex and critical surgical procedures. Controllable 3D volume rendering in virtual reality (VR) is particularly useful to display depth and spatial relationships in volumetric data, and thus to identify specific anatomical landmarks and structural dependencies. However, intuitive control over the medical volume itself, the selection of sectional planes, transfer functions or the rotation or zooming has yet to be explored in depth. In this work, we demonstrate a real-time VR direct volume rendering application for medical images with tangible and intuitive interaction. Our system is real-time capable by the use of efficient volume rendering and foveated rendering techniques. We evaluated the system regarding its performance and gained first insight into the usefulness of a freely grabbable section slice in a preliminary user study.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Human computer interaction (HCI); Human-centered computing; Interaction paradigms; Virtual reality